High Power Density Micro Thermoelectric Generators for Powering IoTs - Aditya S. Dutt; Nithin B Pulumati; Kangfa Deng; Jens Wagner; Andreas Brönner; Frank Ellinger; Gabi Schierning; Kornelius Nielsch; Heiko Reith (Advanced Electronic Materials)
Abstract Micro thermoelectric generators (µTEGs) can harvest waste heat to generate electricity, making them a potential solution to the growing problem of powering autonomous electronics, such as sensors for the Internet of Things. Until now, µTEGs have not been able to provide power for these applications. This is because the output power of µTEGs is limited due to insufficient contacts and poor thermal coupling between the device and the heat source. In this work, the contact resistance as well as the thermal coupling between the heat source and the device through process optimization are improved. The former by improved electrochemical deposition (ECD) conditions, the latter by introducing a thin solder adhesion layer, which smooths the uneven surface of µTEG due to its good wetting properties. Using these improvements in combination with optimized packing density, here the fabrication and characterization of a µTEG with 126 leg pairs connected in series are reported that exhibits an open circuit voltage of 339.2 mV at a temperature difference of 20.6 K and a record‐high normalized power density of 25.1 µW cm−2 K−2 for ECD based µTEGs. This µTEG is used to power a temperature sensor, bringing this work one step closer to application.